Progressive inequality : rich and poor in New York, 1890-1920 - Huyssen, David, 1979- (Harvard University Press, 2014)
Huyssen interweaves dramatic stories of wealthy and poor New Yorkers at the turn of the twentieth century, uncovering how initiatives in charity, labor struggles, and housing reform chafed against social, economic, and cultural differences. A major contribution to the history of American capitalism, Progressive Inequality makes tangible the abstract dynamics of class relations and opens a rare window ontocurrenteconomic and social debates.